Find answers to your questions faster and easier with IDNLearn.com. Find the solutions you need quickly and accurately with help from our knowledgeable community.
Sagot :
Let's start by simplifying the given expression step-by-step:
Given expression:
[tex]\[ \frac{(4 m^2 n)^2}{2 m^5 n} \][/tex]
1. First, simplify the numerator [tex]\((4 m^2 n)^2\)[/tex]:
[tex]\[ (4 m^2 n)^2 = (4)^2 \cdot (m^2)^2 \cdot (n)^2 \][/tex]
Calculating each part separately:
[tex]\[ 4^2 = 16 \][/tex]
[tex]\[ (m^2)^2 = m^{2 \cdot 2} = m^4 \][/tex]
[tex]\[ n^2 = n^2 \][/tex]
So,
[tex]\[ (4 m^2 n)^2 = 16 m^4 n^2 \][/tex]
2. Next, substitute the simplified numerator back into the original expression:
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} \][/tex]
3. Simplify the denominator:
[tex]\[ 2 m^5 n \][/tex]
4. Now, divide each term in the numerator by the corresponding term in the denominator:
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} \][/tex]
Separate the fraction:
[tex]\[ \frac{16}{2} \cdot \frac{m^4}{m^5} \cdot \frac{n^2}{n} \][/tex]
Calculate each part:
[tex]\[ \frac{16}{2} = 8 \][/tex]
[tex]\[ \frac{m^4}{m^5} = m^{4-5} = m^{-1} \][/tex]
[tex]\[ \frac{n^2}{n} = n^{2-1} = n \][/tex]
So,
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} = 8 m^{-1} n \][/tex]
Therefore, the expression equivalent to the given expression is:
B. [tex]\(8 m^{-1} n\)[/tex]
Given expression:
[tex]\[ \frac{(4 m^2 n)^2}{2 m^5 n} \][/tex]
1. First, simplify the numerator [tex]\((4 m^2 n)^2\)[/tex]:
[tex]\[ (4 m^2 n)^2 = (4)^2 \cdot (m^2)^2 \cdot (n)^2 \][/tex]
Calculating each part separately:
[tex]\[ 4^2 = 16 \][/tex]
[tex]\[ (m^2)^2 = m^{2 \cdot 2} = m^4 \][/tex]
[tex]\[ n^2 = n^2 \][/tex]
So,
[tex]\[ (4 m^2 n)^2 = 16 m^4 n^2 \][/tex]
2. Next, substitute the simplified numerator back into the original expression:
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} \][/tex]
3. Simplify the denominator:
[tex]\[ 2 m^5 n \][/tex]
4. Now, divide each term in the numerator by the corresponding term in the denominator:
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} \][/tex]
Separate the fraction:
[tex]\[ \frac{16}{2} \cdot \frac{m^4}{m^5} \cdot \frac{n^2}{n} \][/tex]
Calculate each part:
[tex]\[ \frac{16}{2} = 8 \][/tex]
[tex]\[ \frac{m^4}{m^5} = m^{4-5} = m^{-1} \][/tex]
[tex]\[ \frac{n^2}{n} = n^{2-1} = n \][/tex]
So,
[tex]\[ \frac{16 m^4 n^2}{2 m^5 n} = 8 m^{-1} n \][/tex]
Therefore, the expression equivalent to the given expression is:
B. [tex]\(8 m^{-1} n\)[/tex]
Your presence in our community is highly appreciated. Keep sharing your insights and solutions. Together, we can build a rich and valuable knowledge resource for everyone. For dependable answers, trust IDNLearn.com. Thank you for visiting, and we look forward to assisting you again.